Freezing of few nanometers water droplets - Alireza Hakimian (Nature Portfolio, 2021)
Ice nucleation in confined geometries is a ubiquitous phenomenon, but difficult to characterize. Here the authors investigate experimentally the freezing of water nanodroplets surrounded by octane in nanopores down to 2 nm, and demonstrate that the soft curved oil-water interface suppresses heterogeneous ice nucleation, which occurs at a lower temperature than homogenous bulk nucleation.